COVID-19 Patient Psychological Pain Factors - Zhengkai, Niu; Yajing, Shen (Frontiers in Psychology, 2021)
COVID-19 patients were investigated in this study to assess their levels of psychological distress. Correlation analysis, univariate analysis, and multivariate regression analysis were conducted to find that many factors affect the psychological states of patients with the novel “crown” pneumonia, including the severity of the disease, the surrounding environment, and family health problems. Psychological intervention is proposed to manage post-traumatic effects in COVID-19 patients and help them integrate into the normal life and work as soon as possible after recovering from the disease.